Endoscopic Management of Giant Walled-Off Pancreatic Necrosis With a High Risk of Bleeding. Issue 8 (29th August 2019) - Alhasan, Faysal; Hoilat, Gilles Jadd; Malas, Waddah; Mahmood, Syed K.; Zivny, Jaroslav; Alsayid, Muhammad
ABSTRACT: Walled-off pancreatic necrosis (WOPN) is one of the late complications of acute pancreatitis. We present a 37-year-old man who developed a large WOPN 6 weeks after treatment of severe complicated pancreatitis. Imaging studies revealed a necrotic retroperitoneal fluid collection measuring 27 × 12 × 27 cm with large crossing blood vessels. Cystogastrostomy was performed using a lumen-apposing metal stent. He underwent multiple necrosectomies with significant improvement in the cyst size. Bleeding is a major complication of direct endoscopic necrosectomy; hence, specific imaging and a careful approach should be taken into consideration, especially in WOPN with a high risk of bleeding.